2019
DOI: 10.1515/jisys-2017-0127
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Face Recognition System Using Cuckoo Search

Abstract: The development of an effective and efficient face recognition system has always been a challenging task for researchers. In a face recognition system, feature selection is one of the most vital processes to achieve maximum accuracy by removing irrelevant and superfluous data. Many optimization techniques, such as particle swarm optimization (PSO), genetic algorithm (GA), ant colony optimization, etc., have been implemented in face recognition systems mainly based on two feature extraction methods: discrete co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Experimental results proved the superiority of proposed method (97.5% recognition rate with just 24 features) over other leading optimization techniques such as CS (97% with 48 features), GA(96.5% with 28 features) and PSO (96.5% with 28 features). They further carried forward their research in 2017 in whichPreeti et al [33]suggested anFR system using the Cuckoo Search (CS) optimization technique where features were extracted using combination of PCA and DCT in order to achieve high accuracy rates. Results show that CS gave 88% recognition rate with 10 features only which are equivalent to just 10% of the features used in PCA and gave 96.50% recognition rate with just 34 features which is approximately 35% of the features used in DCT-PCA approach.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Experimental results proved the superiority of proposed method (97.5% recognition rate with just 24 features) over other leading optimization techniques such as CS (97% with 48 features), GA(96.5% with 28 features) and PSO (96.5% with 28 features). They further carried forward their research in 2017 in whichPreeti et al [33]suggested anFR system using the Cuckoo Search (CS) optimization technique where features were extracted using combination of PCA and DCT in order to achieve high accuracy rates. Results show that CS gave 88% recognition rate with 10 features only which are equivalent to just 10% of the features used in PCA and gave 96.50% recognition rate with just 34 features which is approximately 35% of the features used in DCT-PCA approach.…”
Section: Feature Selectionmentioning
confidence: 99%
“…These works mainly use some features like Gabor features [12], wavelet [14] and fused them with dimensionality reduction techniques like LDA [12] or PCA [5] and then used classifiers like SVM citea31 or ANN [12], [14], [5]. In addition to this, many techniques reported in the literature have implemented nature-inspired optimization techniques like cuckoo search [13], PSO (Particle Swarm Optimization) [32] for face recognition. Recently, due to the promising success of deep architectures like CNN (Convolutional Neural Network), researchers have started using these architectures for face recognition.…”
Section: Fig 2: Flow Of Feature Extractionmentioning
confidence: 99%
“…Such algorithms are developed on the basis of physical and biological system's behaviour that exist in nature. Examples include genetic algorithms (GA) (Harandi et al, 2004), Differential Evolution (DE) (Khushaba et al, 2008; Yang et al, 2016), Cuckoo Search (CS) (Malhotra & Kumar, 2019), particle swarm optimization (PSO) (Ramadan & Abdel‐Kader, 2009), harmony search, and so on. Apart from these, new hybrid algorithms are reported by researchers to improve the recognition and selection accuracy.…”
Section: Introductionmentioning
confidence: 99%